2018
DOI: 10.1093/hmg/ddy420
|View full text |Cite|
|
Sign up to set email alerts
|

Neuregulin 1 type III improves peripheral nerve myelination in a mouse model of congenital hypomyelinating neuropathy

Abstract: Myelin sheath thickness is precisely regulated and essential for rapid propagation of action potentials along myelinated axons. In the peripheral nervous system, extrinsic signals from the axonal protein neuregulin 1 (NRG1) type III regulate Schwann cell fate and myelination. Here we ask if modulating NRG1 type III levels in neurons would restore myelination in a model of congenital hypomyelinating neuropathy (CHN). Using a mouse model of CHN, we improved the myelination defects by early overexpression of NRG1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 96 publications
2
46
0
Order By: Relevance
“…PMP2 has have high binding affinity to fatty acids and cholesterol [137,138] and is proposed to participate in fatty acid transport and fatty acid metabolism [133,139,140]. Interestingly, several PMP2 mutations were shown to cause a demyelinating form of Charcot-Marie-Tooth disease [141][142][143]; and upregulation of axonal neuregulin signaling causes an increase in PMP2 expression [144,145].…”
Section: Fatty Acid Uptakementioning
confidence: 99%
“…PMP2 has have high binding affinity to fatty acids and cholesterol [137,138] and is proposed to participate in fatty acid transport and fatty acid metabolism [133,139,140]. Interestingly, several PMP2 mutations were shown to cause a demyelinating form of Charcot-Marie-Tooth disease [141][142][143]; and upregulation of axonal neuregulin signaling causes an increase in PMP2 expression [144,145].…”
Section: Fatty Acid Uptakementioning
confidence: 99%
“…Interestingly, administration of exogenous NRG1 type III and NRG1 type I promotes neurite outgrowth and nerve regeneration (Mahanthappa et al, 1996; Cai et al, 2004). Moreover, modulation of NRG1 activity in animal models of CMT1A (Fledrich et al, 2014), CMT1B (Scapin et al, 2018) and Congenital Hypomyelinating Neuropathy (Belin et al, 2018), can ameliorate the peripheral hypomyelination observed in these diseases, prevent axonal loss and promote nerve functional recovery, the latter all features observed also after nerve injury. Nonetheless, it has also been recently reported that NRG1 is already highly expressed in nerves of CMT1A pre-clinical models, thus indicating that delivery of exogenous NRG1 should be carefully evaluated (Fornasari et al, 2018).…”
Section: Neuregulin-1mentioning
confidence: 99%
“…P2 is a Schwann cell-specific protein expressed in the PNS myelin of tetrapods (10). Intriguingly, P2 is expressed in a mosaic fashion, not being present in all myelin sheaths (11,12). This small βbarrel protein belongs to the family of fatty acid binding proteins (FABPs).…”
mentioning
confidence: 99%